Minimally Invasive Subfrontal Approach: How to Make it Safe and Effective from the Olfactory Groove to the Mesial Temporal Lobe - Mattogno, Pier Paolo; Guerrini, Francesco; Nicolosi, Federico; Panciani, Pierpaolo; Olivi, Alessandro; Fontanella, Marco; Spena, Giannantonio (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Different surgical approaches have been developed to manage lesions of the anterior and middle skull base areas. Frontal, pterional, bifrontal, and fronto-orbito-zygomatic approaches are traditionally used to reach these regions. With advancements in the neurosurgical field, skull opening should be simple and as minimally invasive as possible, tailored on the surgical corridor to the target. The supraorbital approach and the “keyhole” concept have been introduced and popularized by Axel Perneczky starting from 1998 and are now considered a part of everyday practice. The extended possibilities of this surgical route, considering the reachable targets and surgical limits, are described and systematically analyzed, including a description of the salient surgical anatomy, presenting different illustrative cases.Methods and Results Different illustrative cases are presented and discussed to underline the potentials and limits of the minimally invasive subfrontal approach (MISFA) and the possibilities to tailoring the craniotomy on the basis of the targets: extra-axial lesions with different localizations (anterior roof of the orbit, olfactory groove, tuberculum sellae, medial third of the sphenoid wing, anterior and posterior clinoid process), deeper intra-axial lesions (gyrus rectus, medial temporal lobe-uncus-amygdala-anterior hippocampus), and vascular lesions (anterior communicating aneurysm). Each case has been preoperatively planned considering the anatomical and radiologic features and using virtual simulation software to tailor the best possible corridor to reach the surgical target.Conclusions The MISFA is a safe multicorridor approach that can be used efficiently to manage lesions of the anterior and middle skull base areas with extremely low approach-related morbidity.
Keywords: minimally invasive subfrontal approach; key hole craniotomy; upsurgeon